Association between nurturing care practices and weight gain among acutely ill children aged 6–24 months: a cross-sectional study - Putri, Cechillia Icha; Haryanti, Fitri; Sandhi, Ayyu; Akhmadi, Akhmadi (Universitas Muhammadiyah Purwokerto, 2026)
Background: The period between 6 and 24 months represents a critical window for child growth, during which vulnerability to acute illness is high. Acute illness may disrupt normal growth trajectories; however, evidence on the role of nurturing care practices in supporting weight gain during illness remains limited. Objective: This study aimed to examine the association between maternal nurturing care practices and weight gain among acutely ill children aged 6–24 months. Method: A cross-sectional study was conducted at Banguntapan II Primary Health Center, Bantul District, Indonesia. A total of 58 mother–child dyads were recruited using consecutive sampling. Maternal nurturing care practices were assessed using a modified Knowledge, Attitude, and Practice questionnaire based on the World Health Organization nurturing care framework. Child weight gain was evaluated using World Health Organization growth standards. Associations were analyzed using chi-square tests and odds ratios with 95% confidence intervals. Results: No statistically significant association was observed between nurturing care practices and weight gain (p = 0.069; OR = 0.371; 95% CI: 0.126–1.091). However, a higher proportion of children receiving good nurturing care achieved normal weight gain (70.0%) compared with those receiving poor care (46.4%), indicating a potential protective trend. Maternal education and family income were not significantly associated with nurturing care practices or child weight gain. Conclusion: Although no statistically significant association was identified, nurturing care practices showed a potential protective trend in supporting weight gain during acute illness. These findings highlight the importance of integrating nurturing care into sick-child management and underscore the need for longitudinal studies to better understand growth recovery following illness episodes.